Response of onion (Allium cepa) and garlic (Allium sativum) to irrigation with different salinity waters with or without mitigating salinity stress at seedling establishment stage - Chauhan, C.P.S; Shisodia, P K; Minhas, P S; Chauhan, R S (The Indian Journal of Agricultural Sciences, 2007)
The field experiment was conducted for 3 years (1999-2002) on a sandy loam soil at the experimental farm of college in Bichpuri, Agra to assess the salt tolerance of onion (Allium cepa L.) and garlic (Allium sativum L.) using different salinity waters (ECiw 2-8 dS/m). In response to canal water the relative yields of onion averaged 97,71,55 and 33 % with ECiw 2,4,6 and 8 dS/m respectively while the corresponding yields of garlic was 93, 85,65 and 5 1 %. The relative yields of onion improved to 99, 84, 68 and 56 % when saline waters were applied after canal water irrigation at transplanting. The piece-wise linear response functions showed the threshold salinity (ECt) to be 2.9,3.4 and 2.6 dS/m for onion and garlic inigated with saline waters throughout and onion irrigated with saline waters after canal water irrigation at transplanting respectively, while the per cent decline in yield with each unit increase in salinity beyond ECt were 12.7, 10.8 and 9.6 respectively.